Traditional Fishing Methods of Bhutan - Procter, Dennis L; Drukpa, Karma; Yargay, Lobzang Rinzin; Namgey, Rinzin; Zangmo, Sonam; Rai, Surendra K; Suberi, Sudarshan; Phuntsho, Tashi; Thinley, Tenzin; Tangbi, Yeshey D; Dema, Yeshey (Journal of Wetlands Ecology, 2012)
Traditional fishing techniques, practiced in all parts of Bhutan, are described and compared with techniques reported from Nepal. While a wide range of techniques is found in Bhutan, the number is significantly smaller than that from Nepal. For example, six kinds of net are reported from Nepal, but only one from Bhutan. However, the difference in number may reflect in part the limited scope of the present study. At the same time, several techniques appear unique to Bhutan, and others, while similar to their Nepali equivalents, use different materials - plant-derived poisons are an example. Some techniques may have been brought by ancient immigrants from Tibet, with more recent introductions from lowland India and, most recently, from Nepal. DOI: http://dx.doi.org/10.3126/jowe.v6i0.6081 J Wet Eco 2012 (6): 25-30